Analisis Kreativitas Anak Usia 5-6 Tahun Di UPT TK Negeri Satu Atap 01 Lubuk Pakam - Sabina Haliza Putri; Anada Leo Virganta (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the creativity of children aged 5–6 years in collage activities at UPT TK Negeri Satu Atap 01 Lubuk Pakam. Materials and methods. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving 15 children and one classroom teacher. The aspects of creativity examined include fluency, flexibility, originality, elaboration, and evaluation. Results. The findings reveal that children demonstrate good creativity, particularly in fluency and flexibility, as seen in their ability to generate ideas, adapt to different situations, and choose diverse materials. However, originality, elaboration, and evaluation skills still require reinforcement through more varied materials and greater freedom to experiment. Supporting factors for creativity development include flexible time allocation, teacher encouragement, and a conducive classroom environment. In contrast, limiting factors involve restricted collage materials and overly specific teacher examples. Conclusions. The study concludes that collage activities can effectively foster creativity in early childhood when children are given both freedom and material variety.